Crystal structure analysis of an A-DNA fragment at 1.8 A resolution: d(GCCCGGGC). - Heinemann, U (1987)
Single crystals of the self-complementary octadeoxyribonucleotide d(GCCCGGGC) have been analysed by X-ray diffraction methods at a resolution of 1.8 A. The tetragonal unit cell of space group P4(3)2(1)2 has dimensions of a = 43.25 A and c = 24.61 A and contains eight strands of the oligonucleotide. The structure was refined by standard crystallographic techniques to an R factor of 17.1% using 1359 3 sigma structure factor observations. Two strands of the oligonucleotide are related by the crystallographic dyad axis to form a DNA helix in the A conformation. The d(GCCCGGGC) helix is characterized by a wide open major groove, a near perpendicular orientation of base pairs to the helix axis and an unusually small average helix twist angle of 31.3 degrees indicating a slightly underwound helix with 11.5 base pairs per turn. Extensive cross-strand stacking between guanine bases at the central cytosine-guanine step is made possible by a number of local conformational adjustments including a fully extended sugar-phosphate backbone of the central guanosine nucleotide.